COMPARATIVE STUDY OF INTEREST IN READING INTEGRATED SCIENCE BOOKS AND LOCAL WISDOM-BASED LEAFLET MEDIA - Fausan, Sultan Ahmad; Arham, Zul; ., Ismaun (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
Reading is an activity of examining the meaning or essence of a reading with the aim of developing one’s knowledge and potential. Along with the development of times and technology and with advances in this digitalization era, there is a fairly common problem, namely the decline in the percentage of interest in reading. Especially in Indonesia, the number of interest in reading is quite low. This research aims to find out: 1) Students' reading interest in science books 2) Students' reading interest in leaflet media with the theme of local wisdom of the Tolaki tribe, 3) The difference in students' reading interest in science books and leaflet media with the theme of local wisdom of the Tolaki tribe. The sample used was 72 students. Data collection was carried out by means of observation, documentation, and questionnaires. Quantitative research approach with comparative research type. The results showed: 1) Students' reading interest in science books is in the high category with an average reading interest of 58.86. 2) Students' reading interest in leaflet media with the theme of local wisdom of the Tolaki tribe is in the high category with an average reading interest of 85.19 3) There is a significant difference between students' reading interest in science books and students' reading interest in leaflet media with the theme of local wisdom of the Tolaki tribe with a comparison of the average interest in reading science books (58.86) and leaflet media with the theme of local wisdom of the Tolaki tribe (85.19). To conclude, there is a significant difference between students' reading interest in Integrated Science books and students' reading interest in leaflet media with the theme of local wisdom of the Tolaki tribe in class VIII students of SMPN 1 South Konawe.